Association Between Screen Time, Vitamin A Consumption Behavior, and Computer Vision Syndrome in Preclinical Medical Students - Prasetya, Harka; Rahmawati, Atik; Andira, Aisyah Putri; Suparmi, Suparmi (Faculty of Medicine, Universitas Padjadjaran, 2024)
Computer Visual Syndrome (CVS) refers to visual disturbances induced by electronic media such as computers, laptops, tablets, and smartphones. This research aimed to determine the association between screen time, vitamin A consumption behavior, and CVS symptoms among preclinical medical students. Ninety-five students from a single class at the Faculty of Medicine, Universitas Islam Sultan Agung, Indonesia, participated in this cross-sectional study. Data were collected using an online survey platform in February 2022. The screen time, vitamin A consumption behavior, and CVS were measured using a validated questionnaire. The average daily screen time of the respondents was more than 10 h, with the majority having a moderate vitamin A consumption patterns (66.3%) and experienced CVS (63.2%). The most prevalent CVS symptom identified among these respondents was eye fatigue (62.1%), while double vision and inflamed or watery eyes were the least reported CVS symptoms (9.5% and 8.4%, respectively). The Chi-Square test revealed that there was no correlation between screen time and CVS (p > 0.05), but there was a significant correlation between vitamin A consumption and CVS (p < 0.05). In conclusion, CVS is observed among preclinical medical students due to increased screen time and decreased vitamin A consumption. Therefore, there is a need to develop strategies to manage screen time and vitamin A consumption among students at risk for developing a CVS during their academic careers.